International medical electives during and after the COVID-19 pandemic - current state and future scenarios: a narrative review - Maximilian Andreas Storz (Globalization and Health, 2022)
Abstract Background International medical electives are an important and popular component of the academic curriculum in many medical schools and universities worldwide. The purpose of abroad electives is to provide medical students with an opportunity to gain a better understanding of education and healthcare in an international context. The COVID-19 pandemic, however, has substantially changed the international elective landscape. Travel restrictions, closures of international elective programs and the expansion of virtual methods for education caused a widespread disruption to abroad electives. A comprehensive analysis with regard to other consequences for abroad electives, however, has not been done before. Thus, we sought to a) summarize the current transformation of the international medical elective and b) to address potential challenges for post-pandemic international medical electives. Methods The methodology employed is a multidisciplinary narrative review of the published and grey literature on international electives during the last two years of the COVID-19 pandemic. Results Students worldwide had electives postponed or canceled. Apart from evident immediate pandemic-related consequences (such as the substantial decline in global electives and impaired elective research opportunities for educators), there are other several problems that have received little attention during the last two years. These include challenges in the elective application process, poorly-understood consequences for host institutions, and growing global (ethical) disparities that are likely to increase once elective programs will gradually re-open. There is ample evidence that the post-pandemic elective landscape will be characterized by increasing elective fees, and a more competitive seat-to-applicant ratio. Ethical problems for international electives arising from an unequal global vaccine distribution will pose an additional challenge to students and elective coordinators alike. Conclusion The COVID-19 pandemic transformed the international medical elective landscape in an unprecedented way, and future generations of medical students will face a series of additional challenges when applying for global medical electives.